Susceptibility of clinical isolates of Campylobacter pyloridis to 11 antimicrobial agents. - McNulty, C A (1985)
The activities of 11 antimicrobial agents, including two bismuth salts, against 70 strains of Campylobacter pyloridis isolated from gastric biopsy specimens were tested. The isolates were very susceptible to penicillin (the MIC for 90% of the strains tested [MIC90] was 0.03 microgram/ml), erythromycin, cefoxitin (MIC90, 0.12 microgram/ml), gentamicin, and ciprofloxacin (MIC90, 0.25 microgram/ml). The bismuth salts and nalidixic acid had moderate activity (MIC90, 16 to 64 micrograms/ml). Twenty percent of the isolates were resistant to metronidazole (MIC, greater than 1 micrograms/ml), and all were resistant to sulfamethoxazole and trimethoprim (MIC90, greater than 256 micrograms/ml).